Modulation of Angiogenesis by Inflammatory Markers and the Role of Matrix Metalloproteinases in an Endothelial Cell/Fibroblast Co-culture System - A. Barron, Gemma; Bordet, Elise; Goua, Marie; Bermano, Giovanna (Current Angiogenesis (Discontinued), 2014)
Increased levels of inflammatory markers such as tumour necrosis factor-α (TNFα) and interleukin- 6 (IL-6) have been associated with formation of new blood vessels, or angiogenesis, and linked to chronic inflammation in obesity. This study aimed to establish and use a versatile co-culture cell system to further investigate the role of TNFα and IL-6 in modulating (i) tubule formation and (ii) cell-cell interactions via matrix metalloproteinase (MMP) enzyme activity and secretion of vascular endothelial growth factor (VEGF), E-selectin and prostaglandin E2 (PGE2). Co-cultures of human endothelial cells and fibroblasts were incubated with TNFα (10 ng/mL) or IL-6 (10 ng/mL) added 2 and/or 7 days after co-culture establishment. Cell viability by enzymatic conversion was determined by MTT assay; tubule formation was detected by immunostaining; VEGF, E-selectin and PGE2 expression by ELISA analysis and MMP enzyme activity by gel zymography. Treatmentspecific and time dependent differences in tubule formation were observed: IL-6 significantly increased tubule formation, whilst TNFα significantly inhibited tubule formation. Treatment-specific differences in levels of MMP activities which correlate to tubule formation were also observed. This study showed inflammatory markers, typically associated with obese status, affect tubule formation differently in a heterogeneous cell environment similar to that observed in vivo.
Keywords: obesity